Challenges in the Treatment of Xanthoma Disseminatum: Improvement in Disfiguring Facial Lesions with Cladribine and Brief Updated Literature Review - Ren M; Kang L (Clinical, Cosmetic and Investigational Dermatology)
Mingyang Ren, Li Kang Department of Dermatology, BenQ Medical Center, The Affiliated BenQ Hospital of Nanjing Medical University, Nanjing, Jiangsu, People’s Republic of ChinaCorrespondence: Li Kang, Email kangli100828@163.comAbstract: Xanthoma disseminatum (XD) is a rare normolipidemic mucocutaneous xanthomatosis that falls within the spectrum of cutaneous non-Langerhans cell histiocytosis. The management of XD poses significant challenges due to the limited availability of clinical data. Here, we report a case of XD with disfiguring facial involvement that showed marked improvement following treatment with cladribine. The patient tolerated the treatment well, with no significant adverse effects observed except for a transient decrease in white blood cell count, which normalized after symptomatic treatment with appropriate oral medications. Additionally, we provide an updated review of the literature on the use of cladribine in XD. Through this case report and literature review, we aim to underscore both the potential benefits and limitations of cladribine therapy for patients with XD. Furthermore, we emphasize the critical importance of effective interdisciplinary collaboration between dermatology and oncology for the optimal management of this condition.Keywords: xanthoma disseminatum, disfiguring facial lesions, cladribine, adverse events